A highly selective ratiometric fluorescent probe for the sensitive detection of hypochlorous acid and its bioimaging applications. Issue 69 (6th July 2016) - Shu, Wei; Jia, Pan; Chen, Xingzhu; Li, Xueyan; Huo, Yanru; Liu, Fang; Wang, Zuokai; Liu, Caiyun; Zhu, Baocun; Yan, Liangguo; Du, Bin
Abstract : A rapid-response, highly selective and ratiometric fluorescent probe was synthesized to sensitively detect HOCl in living cells. Abstract : The development of simple techniques for monitoring hypochlorous acid (HOCl) in living cells is urgently needed to disclose the important roles of HOCl in biological systems. Although a number of fluorescent probes have been exploited to detect HOCl, most of them are easily influenced by other competing reactive oxygen species (ROS) and reactive nitrogen species (RNS), and disturbed by many factors including variabilities in excitation, probe distribution and environmental conditions due to the recognition of HOCl based on the fluorescence changes in single wavelength. Herein, in this work, we present a simple fluorescent probeAETU-HOCl containing a new recognition group (2-amino-ethyl)-thiourea (AETU) for the ratiometric detection of HOCl in living cells. ProbeAETU-HOCl exhibits outstanding selectivity for HOCl over other ROS/RNS at higher concentrations (0.5 mM, 100 equiv.). More importantly, the rapid response (1 min) and high sensitivity (a detection limit of 3.9 nM) allow it to successfully visualize the intracellular HOCl levels by the ratiometric imaging. The present study would offer a simple, ratiometric, rapid, and ultrasensitive assay for the accurate determination of HOCl in the biological systems.